Post-extrasystolic potentiation differentiates “true” from “pseudo” Low-flow, Low-gradient aortic stenosis - Vanderheyden, Marc; Verstreken, Sofie; Goethals, Marc (Journal of Cardiology and Cardiovascular Medicine, 2020)
Post-extrasystolic potentiation (PESP) is a marker of contractile reserve and refers to the augmentation of left ventricular contractility due to preload recruitment and rise in intracellular calcium following a premature beat. In this case report we show that PESP might be a safe and helpful aid to evaluate low flow, low gradient aortic stenosis and contractile reserve in the cathlab, thereby reducing the potential risk of complications associated with intravenous dobutamine evaluation and reducing unnecessary testing.